Functional Pearl: F for Functor - Hinze, R; Hackett, J; James, D (2012)
Teacher: Last week I held a tutorial series with my students on the concept of a functor, with the purpose of taking a fresh look from a few angles they hadn’t considered before. Lisa: We started gently, but soon built up a heady tower of abstraction, freely wielding the force of functoriality. Harry: For a newcomer to category theory, I can’t believe how much I learnt. And we were having so much fun, we even continued on into the weekend! Teacher: Yes, to finish off our week we looked at how we might describe the printf function in terms of monoidal functors.